2015
DOI: 10.1111/anec.12276
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Virtual Planar QRS and T Vectors Derived from Holter in the Populations with and without Diabetes Mellitus

Abstract: Aims: Research related to type 2 diabetes mellitus (DM) and parameters of electrocardiography (ECG) was limited. Patients with and without DM (NDM) were randomly enrolled in a study to exploit the influence of DM on planar QRS and T vectors derived from the Virtual Holter process.Methods: A total of 216 (NDM) and 127 DM patients were consecutively and randomly recruited. We selected a 1-minute length of ECG, which was scheduled for analysis at 4 AM. After a series of calculating algorisms, we received the virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
1
0
1
Order By: Relevance
“…Because previous studies showed that the frontal QRS-T angle was higher in the patients with hypertension and diabetes mellitus, 20,24,25 we did not include patients with hypertension and diabetes mellitus in our study to exclude the possible effects of these diseases on frontal QRS-T angle. In addition, drugs that are used in the treatment of COPD may change the myocardial repolarization.…”
Section: Limitationsmentioning
confidence: 99%
“…Because previous studies showed that the frontal QRS-T angle was higher in the patients with hypertension and diabetes mellitus, 20,24,25 we did not include patients with hypertension and diabetes mellitus in our study to exclude the possible effects of these diseases on frontal QRS-T angle. In addition, drugs that are used in the treatment of COPD may change the myocardial repolarization.…”
Section: Limitationsmentioning
confidence: 99%
“…При анализе плоскостных углов QRS-T, полученных из 1-минутного фрагмента холтеровской ЭКГ, фронтальный угол QRS-T не отличался у лиц с наличием и отсутствием СД, но угол QRS-T в горизонтальной плоскости выше у больных СД (J. Chen и соавт., 2016) [41].…”
Section: ìåõàíèçìû óâåëè÷åíèÿ óãëà Qrs-tunclassified